Simulation game-based learning for cognitive apprenticeship development: a focus on processing speed - Patcharabhorn Sounthornwiboon; Khwanying Sriprasertpap; Prachyanun Nilsook (Cogent Education)
Processing speed is a critical component of cognitive apprenticeship, which is essential for developing cognitive skills for high-pressure environments. This study highlighted the limitations of traditional teaching methods in fostering rapid decision-making skills and proposed a simulation game-based learning (SGBL) model as an innovative instructional approach. It aimed to (1) develop a targeted SGBL model, (2) assess its effectiveness in enhancing cognitive apprenticeship and processing speed and (3) evaluate student satisfaction. The methodology was divided into three phases: a primary study to identify student needs, system design and development, and implementation. The SGBL model included theoretical and practical sessions, encompassing real-world scenario-based games for practicing life-saving skills. The study involved 73 undergraduate students, split into two experimental groups, and utilised a learning achievement test and a satisfaction questionnaire as research instruments. The findings revealed significant improvements in processing speed and learning outcomes (p < .01). Students expressed high levels of satisfaction, indicating the effectiveness and potential applicability of the model in other fields. Future implications include expanding SGBL with AR/VR and multiplayer functions to enhance engagement and applicability.